Investigation on linear description of the char conversion for the process of supercritical water gasification of Yimin lignite. (28th September 2016) - Jin, Hui; Zhao, Xiao; Guo, Simao; Cao, Changqing; Guo, Liejin
Abstract: Lignite gasification in supercritical water has been proved an efficient and clean utilization because of high gas yields. Char conversion process is the rate-determining step for lignite gasification in supercritical water, therefore, the accurate description of the conversion process is of great importance for the reaction optimization. Special attention was paid on the progress of char conversion in the process of lignite gasification. Quartz tube reactor was employed to avoid undesired catalytic effect of the reactor wall and Yimin lignite was choose as feedstock. The experiments were conducted with the operating range of temperature 650–850 °C with 5%–25% concentration. To improve accuracy of kinetic models, volatile and fixed carbon conversion was treated individually. Lignite conversion was simulated by random pore model, non-reacted core model and homogeneous model respectively and volatile process was expressed as a modification based on the data obtained by thermogravimetric analysis. The calculation results showed that the model with non-reacted core model fit coal gasification in supercritical water best and the average error was 3.18%. Highlights: Gasification kinetic of coal was conducted in quartz tube to omit catalytic effect. Emphasis was paid on char conversion progress of Yimin lignite in SCW. A linear description model especially for char conversion in SCW was proposed. Volatile content was used as a modification of the linear description model. Steam TGA results were used for information for SCWG of lignite particle.